The Effect of Competence and Preparedness on the Performance of Dompu Regency BPBD Staff in Disaster Emergency Response - Muhamad Fauzan Fazrin; Mahmud Mahmud; Risca Ariska Ramadhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze and empirically demonstrate the extent of the influence of competence and preparedness on the performance of Dompu Regency BPBD employees during disaster emergency response. Research Method: This quantitative study employed saturation sampling across the entire population of 65 BPBD employees in Dompu Regency. Primary data were collected via a structured Likert-scale questionnaire and analyzed using multiple linear regression analysis. Results and Discussion: The test results demonstrate that competence and preparedness, both individually and collectively, have a positive and significant effect on employee performance. Furthermore, the preparedness variable had a stronger impact on performance than the competency variable. Implications: Local governments and relevant agencies are advised to prioritize development programs that not only enhance cognitive abilities but also strengthen employees’ mental resilience through crisis simulation training and stress management. Originality: This study fills a gap in the literature by focusing on aspects of organizational behavior within the BPBD of a small district with the sociogeographic characteristics of Dompu, complementing previous research that has largely focused on physical disaster infrastructure.